The Effect of Fermentation Duration on Alcohol Content of Local Variety of Kelud Pineapple Tepache - Shalsa Neha Kharisma devi; Budhiretnani, Dwi Ari; Herawati, Elysabet (Journal of Biotechnology and Natural Science, 2025)
The purpose of this study was to obtain data on the effect of fermentation time optimization on alcohol content in Tepache made from local varieties of Kelud pineapple and to evaluate the alcohol content with the consumption safety standards set by BPOM RI to ensure that the product remains safe and suitable for consumption. This study was an experimental study and used a completely randomized design (CRD) method with 4 treatments and 6 replications. Based on the results of the study, it was found that the longer the fermentation duration, the higher the alcohol content produced. In 72-hour fermentation, the highest average alcohol content was recorded at 1.3%, followed by 48-hour fermentation with an average alcohol content of 1%. Meanwhile, 24-hour and 0-hour fermentation recorded an average alcohol content of 0%. According to the provisions of the Food and Drug Supervisory Agency of the Republic of Indonesia (BPOM RI), drinks with an alcohol content of less than 5% are included in the Group A category, which includes types of low-alcohol drinks that are still allowed to be consumed.